J. Everett Lindsay, 1918. - Farrell's Studio (Forsyth County Public Library, 1918)
Source: Booklet, "Winston-Salem, City of Industry," 1918.
J. Everett Lindsay, 1918. Mr. Lindsay was vice president and secretary of The White Star Company, vice president of Hurdle Loan & Insurance Company, and treasurer of Winston-Salem Retail Merchants Association.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth